2020
DOI: 10.3906/tar-1912-58
|View full text |Cite
|
Sign up to set email alerts
|

Effect of morphological components on the herbage yield and quality of quinoa (Chenopodium quinoa Willd.) grown at different dates

Abstract: Introduction Quinoa (Chenopodium quinoa Willd.), which is also known as pseudo-grain, is an annual plant that has been cultivated for thousands of years in the Andes (Cusack, 1984). The seeds of quinoa are rich in protein, minerals, carbohydrates, and antioxidant compounds when compared to cereals, such as corn, oats, rice, and wheat (Repo-Carrasco et al., 2011; Stikic et al., 2012; Ruiz et al., 2014), and they are usually utilized as human food (Bhargava et al., 2007). Therefore, quinoa has been evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…The length of panicles in quinoa plants depends on the growth and differentiation processes that occur in the apical meristem (Garcia et al, 2019). These processes are determined by the genotype, inflorescence type, and fertility conditions in the soil, among others (Temel and Keskin, 2020). Panicle lengths between 22 and 40 cm have been reported (Lopez et al, 2012) and, in this study, we found panicles between 12 and 45.6 cm in length.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The length of panicles in quinoa plants depends on the growth and differentiation processes that occur in the apical meristem (Garcia et al, 2019). These processes are determined by the genotype, inflorescence type, and fertility conditions in the soil, among others (Temel and Keskin, 2020). Panicle lengths between 22 and 40 cm have been reported (Lopez et al, 2012) and, in this study, we found panicles between 12 and 45.6 cm in length.…”
Section: Resultssupporting
confidence: 73%
“…Panicle colors changed during physiological maturity. Hence, other studies on quinoa reported significant decreases in plant height, stem thickness, number of branches, and panicle ratios, as the sowing time progressed (Hirich et al, 2014;Temel and Keskin, 2020). Montes et al (2018) reported that the wide range of colors in the materials evaluated is because the panicle is covered by granular vesicular pubescence rich in calcium oxalate with white, pink, and purple tones that contribute to panicle coloration of each variety.…”
Section: Resultsmentioning
confidence: 96%
“…Harvest dates of plants according to sowing times and harvest time are given in Table 1. Plants were harvested 10 cm above the soil level after leaving 50 cm at the beginning of the plot and one row at the plot edges as edge effects (Acar et al, 2019b;Kır and Temel, 2017;Temel and Keskin, 2020). From the harvested plants, 10 plants were selected to represent the parcel and after drying for a while in the shade, they were allowed to dry in the drying oven at 70 o C until their weight stabilized.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that Atriplex nitens plant has high nutritional values for animals (Watson, 1990;Rabbimov et al, 2011;Acar et al, 2019b). Nutritional value and digestibility of feed are significantly affected by plant species and varieties, environmental factors, cultural practices, sowing times and harvest times (Buxton, 1996;Aganga et al, 2003;Collins and Fritz, 2003;Özyiğit and Bilgen, 2006;Önal Aşcı and Acar, 2018;Temel and Keskin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…), an annual pseudo cereal, is seen as an alternative crop in human and animal nutrition in many regions of the World since it adapts well to different climate and soil conditions and has a high nutritional value (Jacobsen et al, 2007;Geerts et al, 2008;González et al, 2012;Abtahi Adolf et al, 2013;Ruiz et al, 2014;Tan and Temel, 2017a;Tan and Temel, 2018;Temel and Yolcu, 2020). The fact that the seeds and vegetative parts (leaf + stem) having quality fiber, balanced amino acid, high protein and energy content is an important factor in the consideration of the plant as a valuable alternative source of nutrition (González et al, 2012;Rojas and Pinto, 2015;Tan and Temel, 2017b;Tan and Temel, 2019;Temel and Keskin, 2020;Temel and Tan, 2020). is important to determine the most suitable varieties in terms of mineral composition by means of adaptation studies.…”
Section: Introductionmentioning
confidence: 99%